2018
DOI: 10.1111/jcmm.13781
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNAs in brain tumours: Focus on recent epigenetic findings in glioma

Abstract: Glioma biology is a major focus in tumour research, primarily due to the aggressiveness and high mortality rate of its most aggressive form, glioblastoma. Progress in understanding the molecular mechanisms behind poor prognosis of glioblastoma, regardless of treatment approaches, has changed the classification of brain tumours after nearly 100 years of relying on anatomopathological criteria. Expanding knowledge in genetic, epigenetic and translational medicine is also beginning to contribute to further elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 102 publications
(240 reference statements)
0
24
0
Order By: Relevance
“…The expression of these genes also highly correlates with risk score and expression of 7 well-established immune checkpoints. Most of the candidate immune checkpoint genes have been previously associated with glioma [37][38][39]. Kiang et al [40] reported that CRNDE is elevated in glioma and might be modulated by EGFR signaling to promote gliomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of these genes also highly correlates with risk score and expression of 7 well-established immune checkpoints. Most of the candidate immune checkpoint genes have been previously associated with glioma [37][38][39]. Kiang et al [40] reported that CRNDE is elevated in glioma and might be modulated by EGFR signaling to promote gliomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a class of transcripts that are greater than 200 nts in length and lack of coding potential [11,13]. Nowadays, more and more lncRNAs have been suggested to be dysregulated in glioma tissues and involved in regulating glioma cell proliferation, differentiation, apoptosis, cell cycle, and autophagy [21–23,27].…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs are increasingly recognized as important players in cancer research [19], particularly as biomarkers and/or therapeutic targets [32][33][34][35][36], including in brain tumors [20,[37][38][39][40]. However, there is a lack of knowledge of lncRNAs' involvement in MBs.…”
Section: Discussionmentioning
confidence: 99%